2011
DOI: 10.1016/j.tetlet.2010.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Toward the total synthesis of maoecrystal V: an intramolecular Diels–Alder route to the maoecrystal V pentacyclic core with the appropriate relative stereochemistry

Abstract: A diastereoselective route to the maoecrystal V core compound (6) has been achieved. Key transformations include an intramolecular Diels-Alder cyclization and an exo-glycal epoxide rearrangement sequence.The unique and complex structure of maoecrystal V (1, Fig. 1), first isolated by Sun and coworkers in 2004, serves to render it a challenging target for total synthesis. Adding to the level of interest in maoecrystal, is its potent in vitro activity against HeLa cells (IC 50 = 20 ng/ml).1 Particularly notewort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…Peng and Danishefsky reported their approach toward maoecrystal V ( 66 ) in 2011 (Figure ). As part of their route, they made use of a Mukaiyama/Magnus enone α-hydroxylation reaction to install the alcohol of 65 from enelactone 64 , and this was effected in 80% yield with 1.5:1 diastereoselectivity for the desired epimer at 2 mol % catalyst loading.…”
Section: C–o Bondsmentioning
confidence: 99%
“…Peng and Danishefsky reported their approach toward maoecrystal V ( 66 ) in 2011 (Figure ). As part of their route, they made use of a Mukaiyama/Magnus enone α-hydroxylation reaction to install the alcohol of 65 from enelactone 64 , and this was effected in 80% yield with 1.5:1 diastereoselectivity for the desired epimer at 2 mol % catalyst loading.…”
Section: C–o Bondsmentioning
confidence: 99%
“…In 2012, Danishefsky and Peng at Columbia University and the Sloan‐Kettering Institute for Cancer Research reported the second total synthesis20 of maoecrystal V by leveraging the information gathered in their previous studies 12c,i. Their successful synthesis (Scheme ) commenced with the union of ester 34 with 3‐chlorocyclohexenone ( 35 ), followed by the adjustment of oxidation states to afford alcohol 36 .…”
Section: Total Synthesesmentioning
confidence: 99%
“…2012 beschrieben Danishefsky und Peng von der Columbia University und dem Sloan‐Kettering Institute for Cancer Research die zweite Totalsynthese20 von Maoecrystal V, für die sie Informationen aus vorherigen Untersuchungen nutzten 12c,i. Ihre erfolgreiche Synthese (Schema ) begann mit der Verknüpfung des Esters 34 mit 3‐Chlorcyclohexenon ( 35 ), der die Anpassung der Oxidationszustände unter Bildung des Alkohols 36 folgte.…”
Section: Totalsynthesenunclassified